1992
DOI: 10.1021/j100185a057
|View full text |Cite
|
Sign up to set email alerts
|

Addition of ferrocene derivatives to the surface of quantum-confined cadmium sulfide clusters: steady-state and time-resolved photophysical effects

Abstract: DR plots are given for three carbons of series M with increasing degree of oxidation. These results may be summarized as follows:(i) The polarity of the adsorptive prevents the filling of the micropores at low relative pressures as noted by the decrease in slope ratios from N2 to HzO.(ii) The polar moment is not the only factor to explain the deviations (relative to N2) found for SO2, CH30H, and H20 (they have very similar values); neither is the hydrogen bond by itself because is similar for water and methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…30 The effects of different ferrocenyl derivatives on the PL of CdS nanocrystals, stabilized by inverse micelles (rather than TOPO), have also been investigated, and quenching or enhancement of the PL was observed depending on the nature of the ferrocene derivative. 28 The TOPO-capped CdSe nanocrystals used in this work were prepared by the method of Murray et al 33 The absorption feature of these nanocrystals at 530 nm in toluene solution indicates that they have a diameter of approximately 3.4 nm. 33 The PL maximum of these nanocrystals in toluene solution is centred at 545 nm.…”
Section: Solution Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The effects of different ferrocenyl derivatives on the PL of CdS nanocrystals, stabilized by inverse micelles (rather than TOPO), have also been investigated, and quenching or enhancement of the PL was observed depending on the nature of the ferrocene derivative. 28 The TOPO-capped CdSe nanocrystals used in this work were prepared by the method of Murray et al 33 The absorption feature of these nanocrystals at 530 nm in toluene solution indicates that they have a diameter of approximately 3.4 nm. 33 The PL maximum of these nanocrystals in toluene solution is centred at 545 nm.…”
Section: Solution Studiesmentioning
confidence: 99%
“…[25][26][27] The photoluminescence of CdS nanocrystals has been shown to be either quenched or enhanced in the presence of different ferrocenyl derivatives, the enhancement occurring when a dimethylamino-substituted ferrocene was coordinated to the nanocrystal surface via amine ligation. 28 Electrochemical modification of electronic effects of metal nanoparticles by ferrocenyl-derivative capping ligands has also been demonstrated. 29 In addition, it has been shown that ferrocene and ferrocenium can exert different effects on, e.g., the luminescence of organic luminophores.…”
Section: Introductionmentioning
confidence: 99%
“…The same version of the modified KWW function was used by Chandler et al to fit PL decay data in CdS clusters, with ferrocene derivatives on their surface. 55 Beadie et al used the KWW function to fit the carrier's relaxation in CdS x Se 1-x -doped glasses, measured by a pump-probe technique. 56 The latter's model suggests that excited carriers, localized on the surface, can recombine on recombination centers, reached via continuous time random walks.…”
Section: Iv2a a Quantitative Analysis Of The Nanosecond Decaymentioning
confidence: 99%
“…This system is described in detail elsewhere (19). Briefly, excitation was provided by a cavity-dumped tunable dye laser, synchronously pumped with the second harmonic of a mode-locked Nd-YAG (Coherent, Antares).…”
Section: Time Resolved Measurementsmentioning
confidence: 99%